Jawabanmu

2014-06-30T14:38:57+07:00
L i m (1 - tan 2x)tan4x = Lim (1 - tan2x)tan4x 4x
x⇒π/8                             x⇒π/8                      4x
                                     = l i m (4x - tan2x)(4x)(2x)
                                       x⇒π/8                      2x
                                     = l im     4x  - Tan2x (4x)
                                       x⇒π/8  2x      2x
                                     = l i m (2 - 4x)
                                       x⇒π/8
                                     = 2 - 4π/8
                                     = 2 - 1/2 π
                  
1 5 1
2014-06-30T16:42:36+07:00
(1-tan 2x) tan 4x = ((cos 2x/cos 2x) - (sin 2x/cos 2x)) tan 4x
> ((cos 2x-sin 2x)/cos 2x) tan 4x X 4x/4x X 2x/2x
> hasil akhirnya kalau gak salah 4x
> 4(π/8)= π/2
maaf, jawabannya seadanya cuma cob-coba tapi kalo aku caranya udah kayak gitu